The moral foundation of economic behavior - Rose, David C. (New York ; Oxford : Oxford University Press, 2011)
Events ranging from the Enron scandal to our current global financial meltdown remind us that immoral behavior can undermine even the mightiest economies. This book explains why moral beliefs can and likely do play an important role in the development and operation of market economies.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Economics -- Moral and ethical aspects; Cooperation